2014
DOI: 10.1111/apa.12838
|View full text |Cite
|
Sign up to set email alerts
|

Minimal enteral nutrition during neonatal hypothermia treatment for perinatal hypoxic-ischaemic encephalopathy is safe and feasible

Abstract: Early minimal enteral feeding during hypothermia proved feasible, with no significant complications. Delayed enteral feeding did not affect time to full enteral feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 23 publications
3
39
0
1
Order By: Relevance
“…A study of patients with HIE in the UK and Sweden demonstrated that enteral feeding during hypothermia was not associated with increased mortality or morbidity [17]. The authors suggested that the greater number of patients that received human milk (fully breastfed or breastfed and bottle-fed) at discharge in Sweden (85%) versus the UK (67%) may have contributed to the results, but this difference was not statistically significant ( p = 0.08).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of patients with HIE in the UK and Sweden demonstrated that enteral feeding during hypothermia was not associated with increased mortality or morbidity [17]. The authors suggested that the greater number of patients that received human milk (fully breastfed or breastfed and bottle-fed) at discharge in Sweden (85%) versus the UK (67%) may have contributed to the results, but this difference was not statistically significant ( p = 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study on HIE patients, that received delayed enteral feeding in the UK and early enteral feeding during hypothermia in Sweden, demonstrated that enteral feeding during hypothermia was not associated with increased mortality or morbidity [17]. These results suggest that early minimal enteral nutrition (MEN) during hypothermia is feasible and is not associated with significant complications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite adverse gut effects previously noted with HIE, moderate hypothermia has been shown to be gut-protective following ischaemia-reperfusion, 21 22 with a beneficial effect of TH on feed tolerance in neonates. 23 These reports combined with increasing experience in the use of TH, low rates of gut complications in cooled infants (0.7%) 7 and reports suggesting the safety of minimal enteral feeds during TH 18 may have increased confidence in starting enteral feeds during TH. Clinicians were starting feeds particularly in infants with moderate HIE, with no other signs of compromise (ie, need for inotropic support).…”
Section: Discussionmentioning
confidence: 99%
“…16 A survey presented in 2014 reported that 21% of UK neonatal units offered trophic feeds during TH, but lacked data on when milk was introduced, milk type, volumes, frequency and advancement of feeds. 17 Given reports of the safety of small-volume enteral feeds during TH, 18 we hypothesised that rates of enteral feeding would have increased. In this study, we aimed to survey clinicians in UK neonatal units providing active TH for determining current nutritional practices during and after TH in infants with HIE.…”
Section: Introductionmentioning
confidence: 99%
“…22 The Scandinavian protocols and some authors from the USA allow minimal enteral feeding throughout the hypothermia period, and they show reduced time to full feeds and shorter hospital stay without increased risk of complications. 23,24 We also found a significant change in the systemic hemodynamic parameters after rewarming such as increase in the HR, systolic BP and LVO with no significant difference in the LVEF over the various time points during hypothermia and after rewarming. These findings are consistent with other hemodynamic studies on infants with HIE undergoing therapeutic hypothermia that have focused on cardiac and cerebrovascular hemodynamics.…”
Section: Discussionmentioning
confidence: 53%